Stabilization of magnetic suspension system by a reset element (Adjustment of vibration attenuation characteristic) - Yuji ISHINO; Takeshi MIZUNO; Masaya TAKASAKI; Daisuke YAMAGUCHI (Nihon Kikai Gakkai ronbunshu, 2020)
A first-order-reset element (FORE) controller is modified to adjust the vibration attenuation characteristic of a magnetic suspension system. The proportional-derivative (PD) feedback control is the simplest control method of stabilizing magnetic suspension systems. In the PD-controlled system, restoring force is produced with the proportional element and damping effect is produced with the derivative element. Meanwhile, a feedback control using a FORE has been proposed to stabilize magnetic suspension systems. The FORE replaces a linear integrator built into a first-order low-pass filter by a non-linear integrator. The proposed controller can stabilize a magnetic suspension system with one element. The restoring force and damping effect are generated simultaneously. However, the two effects could not be adjusted separately. To adjust the vibration attenuation characteristic, the FORE controller is modified to adjust the transition value at reset. The characteristics of the modified controller are studied through numerical analysis. Then the effectiveness of the modification is demonstrated by several simulations and experiments.